Development of a High-Throughput Diagnosis Method for Detecting the ALDH2 Gene Using Fingernail DNA - Nagayoshi, Emi; Mizuta, Yoko; Takii, Yukio (International Journal of Biotechnology for Wellness Industries, 2013)
A clinical method for effective genetic screening of the aldehyde dehydrogenase 2 (ALDH2) gene was developed, using the fingernail as a source of DNA material. A highly effective protease that could solubilize fingernail keratin and inactivate any DNase co-existing in the tissue was obtained by cloning and sequencing the gene for alkaline protease from Bacillus alcalophilus, followed by expression of the gene in Bacillus subtilis. The amino acid sequence of MIB029 protease contained common regions found in four other subtilisin-like proteases. In the fingernails of 113 female university students (average age 20.8 ± 0.7 years; body mass index, 20.4 ±1.6), ALDH2 frequency was 0.66 for the typical Glu homozygote, 0.32 for the heterozygote (Glu487Lys), and 0.020 for the atypical Lys homozygote. Through a questionnaire, it was found that the subjects had not previously received information regarding the relationship between their genetic background and consumption of alcoholic beverages. We found that the genetic single nucleotide polymorphism (SNP) background to alcoholism can be easily detected by collecting fingernails, which is convenient for subjects or patients.